2021
DOI: 10.1002/jaba.804
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the relation between feedback preferences and performance

Abstract: Performance feedback is a common organizational behavior management intervention (Gravina et al., 2018) that typically yields consistent effects when combined with other procedures (Alvero et al., 2001). A noteworthy characteristic that might affect feedback effectiveness is timing (Lechermeier & Fassnacht, 2018). Given the frequent use and practical utility of feedback, we assessed feedback preference across three feedback timing options: after step, after trial, and after session. We used a direct-choice par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It may be that novel tasks act as an establishing operation that increases the value of information about the task (Bacotti et al, 2021). More specifically, novel tasks could have acted as a transitive conditioned motivating operation that established the reinforcing effectiveness of information (Michael, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It may be that novel tasks act as an establishing operation that increases the value of information about the task (Bacotti et al, 2021). More specifically, novel tasks could have acted as a transitive conditioned motivating operation that established the reinforcing effectiveness of information (Michael, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Selecting corrective feedback was similar to manding for information in an interrupted chain (e.g., Lechago et al, 2013). Conversely, mastered tasks may serve as an abolishing operation for information (Bacotti et al, 2021). Although weak, the present study found some preliminary evidence of shifts in preference from corrective to positive feedback as participants gained proficiency with the task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations